Local oxygen transport resistance in polymer electrolyte fuel cells: origin, dependencies and mitigation - García-Salaberri, Pablo A.; Das, Prodip K.; Chaparro, Antonio M. (Frontiers in Energy Research, 2024)
Next-generation polymer electrolyte fuel cells (PEFCs) require an integral design of the porous structure of electrodes at different scales, to improve performance and enlarge durability while reducing cost. One of today's biggest challenges is the stable, high-performance operation at low Pt loading due to the detrimental effect of the local oxygen transport resistance caused by ionomer around catalyst sites. Hindered local oxygen transport arises from sluggish kinetics at the local reaction environment, that comprises adsorption at (wet) ionomer and Pt interfaces, and diffusivity of gas species in ionomer and water. Diverse factors affect oxygen transport, including operating conditions (relative humidity, temperature, and pressure), ionomer content and morphology, ionomer heterogeneity, porosity of carbon support, catalyst dispersity, and flooding. To attain performance and durability targets, it is essential to maximize the oxygen utilization of the catalyst layer by implementing enhanced membrane electrode assembly (MEA) architectures. This involves employing advanced catalyst layer preparation techniques, including electrospraying, to generate optimized highly porous morphologies. Furthermore, achieving these targets necessitates the development of new materials with tailored properties, such as high permeability and porous ionomers, among other innovative strategies.